Essays in International Macroeconomics and Economic Inequality - Arrigoni, Simone (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2025)
This thesis consists of four essays at the intersection of international macroeconomics and economic inequality. Each chapter tackles important questions aimed at understanding the relevant macroeconomic dynamics between countries, the drivers of within-country wealth inequality, and the implications of their interaction. The thesis primarily consists of empirical contributions that employ various empirical methods, such as panel data models, quantile regressions, probit models, decomposition methods, and local projections. It makes use of different datasets, including macroeconomic data and household surveys. The first essay (Chapter 2) studies the effectiveness and comparative performance of different approaches used to construct Financial Conditions Indices (FCIs) for a broad set of countries. An econometric evaluation shows that FCIs constructed through equal weights combinations of financial variables have good statistical properties and often outperform more sophisticated methods such as factor models with time-varying parameters and principal component analysis. This finding holds both in the context of quantile regressions, where they prove useful in signalling downside risks to economic activity, as well as in probit models, where they show a stronger correlation with future banking crises. Importantly, for the euro area and the United States, these simple indices outperform popular alternatives that rely on larger information sets and different econometric methods, specifically the Composite Index of Systemic Stress (CISS) and the National Financial Conditions Index (NFCI). The findings of this chapter are of particular interest to researchers and institutions interested in monitoring financial conditions in a large number of countries, including those for which data are too short or present too many irregularities to be treated through more formal econometric methods. The second essay (Chapter 3) examines the impact of inherited wealth - inheritances and gifts - on the accumulation of household wealth and its distribution in Ireland. It employs household-level survey data to decompose the Gini coefficient of wealth inequality into the contributions from inherited wealth and other sources of wealth, using the Marginal Gini Decomposition (MGD) methodology. The analysis shows that inheritances in Ireland contribute little to wealth inequality, and may even have reduced it over time, in line with existing findings for Britain and the United States. On the one hand, this finding could be attributed to the importance of inheritances in the acquisition of property assets for middle-wealth households. In proportion to their total wealth, inherited wealth is more significant for the middle and lower parts of the distribution compared to the top one. On the other hand, the flow of inherited wealth has increased over time alongside asset prices, such as house prices. Additionally, inheritors tend to substitute labour income with rental income. The third essay (Chapter 4) investigates whether the advent of financial globalisation has contributed to increasing wealth inequality in the United States, France, and the United Kingdom. Using a fixed effects panel data model, I find that positive changes in the benchmark measure of financial globalisation are associated with a positive change in the top 1% and 10% wealth shares. This result is mainly driven by the concentration of ownership of portfolio equities and financial derivatives, the accumulation of new cross-border financial wealth over time, and differentials in recovery timings during financial crises. This chapter contributes to the discussion around policies such as capital flows management and capital or wealth taxes. The fourth essay (Chapter 5) explores whether household heterogeneity affects the global transmission of monetary policy. I investigate how, and to what extent, inequality influences the way the Fed's monetary policy actions spill over to the real economy in the rest of the world. I employ state-dependent local projections and exploit variation in within-country disposable income inequality across a large panel of countries to estimate the heterogeneous responses of GDP to a monetary policy tightening in the United States. I rationalise these responses and the related mechanisms within a Two-Agent New Keynesian (TANK) model. I find that income inequality affects how foreign GDP responds to a US monetary policy shock. However, greater inequality strengthens the negative spillover effects of the shock on GDP in advanced economies, while it mitigates it in emerging market economies. The theoretical model suggests that this divergence depends on the level of participation in international financial markets. Households in emerging market economies face higher barriers to invest internationally, which increase their foreign bond holding cost. This means that, even with high inequality, households in these countries cannot re-balance their portfolios towards foreign bonds when the shock hits and thus the negative effect of higher inequality on domestic conditions is reduced.
APPROVED
Keywords: international macroeconomics; wealth/income inequality; macroeconomics; financial conditions; inheritance; financial globalisation; monetary policy spillovers